Counterparty credit risk : the new challenge for global financial markets - Gregory, Jon (Chichester, West Sussex : Wiley, 2010)
The book explains the emergence of counterparty risk during the recent credit crisis.
Includes bibliographical references (p. 405-409) and index.
nif 24/04/13
Loans
Keywords: Derivative securities; Risk management; Credit risk